Pemenuhan Hak Atas Jaminan Kesehatan Terhadap Pekerja Swasta dengan Status Probation atau Masa Percobaan di Kota Padang - Mutya, Sherly; Danil, Elwi; Khairani, Khairani (UNES Law Review, 2023)
The fulfillment of workers' rights in the form of health insurance is a program in accordance with the mandate of the Constitution. Realized through Law of the Republic of Indonesia Number 40 of 2004 concerning the National Social Security System regulates the basic rights to a sense of security owned by workers /employees. Among them, the right to welfare includes health insurance programs, work accident insurance (JKK), death insurance (JKM), and old age insurance (JHT). The formulation of the problem in this study is: 1). How is the arrangement or protection of health insurance for private workers with probation status or probation period in Padang City?, 2) Factors that play a role in fulfilling the right to health insurance for workers with probation status or probation period in Padang City?. This research uses normative juridical methods that focus their studies by viewing law as a complete system, including a set of legal principles, legal norms, and legal rules, in this study in addition to using secondary data also using empirical data, but does not eliminate the nature of this research as normative research. The results of this study are: 1) Non-implementation of the Law and all regulations governing health insurance for private workers with Probation status in general, 2) There must be a policy issued by the government strictly regarding the sanctions given if workers do not get health insurance.